Analisa Erosi di DAS Kali Lamong Menggunakan Pendekatan ArcSWAT - Pane, Yasmin Pebriani Sitorus; Sholichin, Mohammad; Asmaranto, Runi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Flood on the downstream and sedimentation at the bottom of the river often occured in Kali Lamong Watershed. From those problems to reduce problems occurin in Kali LamongoWatershed, need new landuse method (scenario) using ArcSWAT as a conservation. To get the result of runoff, erosion, and sedimentation ArcSWAT program need 4 processes : watershed delineation, Hydrological Response Unit (HRU), input database, and simulation. The results showed an average runoff rate of 55.369 mm/tahun, average erosion rate of 31.578 ton/ha/tahun, and average sedimentation rate of 67576.11 m3. The analysis result of the Erosion Hazard Indekx by Hammer (1981), shows that the index at low level (index , 1.0) in an area of 20239.267 ha, medium level (index 1.01-4.0) in an area of 27999.556, high level (index 4.01 – 10.0) in an area of 24166.261 ha. With the conservation that was adjusted to the land capacity of Kali Lamong Watershed, the new land use could reduce runoff by 22.92%, erosion of 22.01%, and sedimentation of 44.55%. Using new land use shows that  the Erosion Hazard Index Kali Lamong Watershed was at low level and medium level. DAS Kali Lamong sering mendapat bencana seperti banjir pada bagian hilir serta pendangkalan dasar sungai akibat laju sedimentasi. Dari permasalahan tersebut maka untuk mengurangi permasalahan pada DAS Kali Lamong diperlukan usaha konservasi dengan merencanakan tata guna lahan yang baru menggunakan model ArcSWAT. Untuk mendapatkan hasil limpasan, erosi, dan sedimentasi model ArcSWAT memerlukan 4 proses yaitu pembuatan delineasi DAS, pengolahan Hydrology Response Unit (HRU), memasukkan database, dan melakukan simulasi. Dari analisa menunjukkan rerata limpasan 55.369 mm/tahun, rerata erosi 31.578 ton/ha/tahun, dan rerata sedimen 67576.11 m3. Hasil analisa Indeks Bahaya Erosi oleh Hammer (1981) diperoleh indeks dengan kriteria rendah (indeks < 1.0) seluas 20239.267 ha, kriteria sedang (indeks 1.01-4.0) seluas 27999.556, kriteria tinggi (indeks 4.01 – 10.0) seluas 24166.261 ha. Hasil dari skenario pembuatan tata guna lahan baru yang disesuaikan dengan kemampuan lahan DAS Kali Lamong menunjukkan penurunan limpasan sebesar 22.92%, erosi sebesar 22.01%, dan sedimentasi sebesar 44.55%. Menggunakan tata guna lahan baru kriteria Indeks Bahaya Erosi DAS Kali Lamong berada di kriteria rendah dan sedang.